Implementation of Problem Based Learning Model on Social Science Subject on Junior High School Students in Semarang, Indonesia - Hamid, Nur; Wijayanti, Nur Rohmah; Yaqin, Mochamad Ainul; Yaqin, Mochamad Ainul; Ningsih, Mega Prani (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to notice the effectiveness of problem-based learning method applied on students at seventh grade in Junior High School 25 Semarang on Social Science subject. Data was gathered through observation, interview, questioner, documentation and student test result. Responds analysis used quantitative descriptive analysis while test result analysis employed t-test. The result of this study showed that problem-based learning method was profoundly beneficial and enjoyable for students. This was demonstrated by the high score shown in student responds indicators encompassing interest, learning responds, cooperation, responsibility, activeness, understanding, and student knowledge after learning process conducted as well as in student achievement which presented a rise. Average score achieved in factual learning was 74.59 while problem-based learning recorded 86.56. The average deviation from those learnings was -11.969. Thus, due to sig> 0.001, there was a deviation on students’ achievement in between factual and problem-based learning.